IMPLEMENTASI MANAJEMEN DESAIN PADA DESAIN ARSITEKTUR DAN DESAIN INTERIOR - Setiadi G S (Universitas Trisakti, 2012)
AbtractThe progress of big cities in Indonesia is developing very rapidly. Therefore facilities run by goverment and private institution complete to beautify public facilities with excellent architectural and iterior designs.On the other hand, competition among architectural and interior design as well as construction service are very competitive in this globalization era. consequently, the demand of professional designers are badly meeded by both goverment and private institution. Thus a project of architecture or interior desing always need a good plan to meet various cases which may arise sistematically.Design is an answer for all things connected to careful planing to produce the ultimate design complying with the clients